Axial compression test on concrete columns hybrid strengthened with CFRP/CPVC tube and ECC cladding layers. (June 2023) - Han, Tianhao; Ji, Jianghao; Dong, Zhiqiang; Zhu, Hong; Wu, Gang
Abstract: Existing research proved that the confinement of fiber-reinforced polymer (FRP) and commercially available chlorinated polyvinyl chloride (CPVC) tubes can considerably improve the strength and ductility of concrete columns. Meanwhile, engineered cementitious composite (ECC), as a kind of high-ductility and high-energy absorbing material, can effectively improve the ductility of concrete columns. In this study, a novel hybrid system was proposed, including the hybrid confinement of carbon fiber-reinforced polymer (CFRP) and CPVC, and an inner ECC layer. Its compressive behavior was explored by the axial compression test, and the effects of the number of CFRP layers, the diameter of the CPVC tubes, and the net spacing of the CFRP strips were considered as the test variables. The test results showed that CFRP-CPVC confinement can significantly improve the peak strength and corresponding strain of cylinders, and the inner ECC layer can enhance the relative ductility. Compared to the diameter of the CPVC tube and the net spacing of CFRP strips, thicker CFRP layers and full CFRP wrapping noticeably improved the loading capacity of the specimens. Finally, a theoretical model was given for predicting the peak axial stress of the specimens, which can provide a reference for designing the hybrid strengthening system.